Answer:
y = 3x
Step-by-step explanation:
(1,3) (2,6)
The first step is to find the rate of change ( or slope)
m = (y2-y1)/(x2-x1)
m = (6-3)/(2-1)
m = 3/1
m = 3
Then we need to use the point slope form of the equation of a line
y-y1 = m(x-x1)
y-3 = 3(x-1)
Distribute the 3
y-3 = 3x-3
Add 3 to each side
y-3+3 = 3x-3+3
y = 3x
The nephew would need to use division to isolate x giving him $66.50 to spend
The answer to this is 244
The answer is b
Hope that helps
Answer:
Hi! The correct answer is x=1/4+y/2!
Step-by-step explanation:
Solve for the first variable in one of the equations, then substitute the result into the other equation